The Function of Old Manuscript Reading and Its Preservation in the Sasak Community of West Sakra District - Lalu Kusnendar Atmanegara; Aswandikari Aswandikari; Saharudin Saharudin (RETORIKA: Jurnal Ilmu Bahasa, 2023)
This research aims to determine the functions and methods of preserving old manuscripts in the Sasak community in the west Sakra district. This research is motivated by the existence of manuscripts that have a function in the culture of the Sasak community in the West Sakra sub-district and proves whether the use of certain manuscripts is limited to community suggestions or whether there are other purposes. Data collection was carried out by observation and interviews with an emic approach and analyzed using functional theory. From the results of the study, it can be concluded that the Jatiswara script serves as a ‘circumcision’ diving ritual for boys because diving is an Islamic process as described in the Jatiswara text, namely the mulene game slam ‘a person’s Islam is not perfect if it has not been circumcised. The Indarjaya script serves as a remedy for people who are ‘unable to speak’. It is depicted in the story of the daughter who could not speak, namely the princess nengke kayun ngandike ‘the princess wants to talk’. While the Selandir script serves as a ritual remedy for kepaq people ‘cannot walk’. It was described in Selandir’s text that reads still lemper bise lumaris ‘still unable to walk. Meanwhile, the manuscript preservation process is carried out in two ways, namely internal and external. Internally, preservation is carried out by direct inheritance and copying of manuscripts. Meanwhile, external preservation is carried out by establishing customary institutions, puppetry, digitization, translation, and transformation of manuscripts.